Analyzing Grammatical Errors in The Undergraduate Thesis of Students of The Department of Arabic Language Education at Sultan Sharif Qasim Islamic State University Riau In 2017 - Siti Nurdinah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to detect grammatical errors in the undergraduate thesis of students of the Department of Arabic Language Education at Sultan Sharif Qasim Islamic State University Riau in 2017. The design of this research is a descriptive qualitative research. The data collection tools are the official documents method. In this research, the researcher analyzed the grammatical errors in the university thesis, where the researcher went through three stages, namely: 1- Recognizing the error, the researcher looked at the texts of the supplementary research written in Arabic for students of the Department of Arabic Language Education at Sultan Sharif Qasim Islamic State University in 2017, and identified the errors in which the students deviated from the grammatical rules. 2 - Correcting the error, the researcher clarified what is correct 3 - Clarifying the error, the researcher clarified what are the correct rules in the Arabic language. The results of this research are: The grammatical errors made by the students of the Department of Arabic Language Education at Sultan Sharif Qasim Islamic State University, Riau, in writing the supplementary research are many, including those related to the section of marfu’at, manshubat, majrurat, majzumat, asma` ma’rifah, tawabi’ and murakkabat. The researcher found forty-nine errors in the section of tawabi’ (na’at haqiqy) and forty errors in the section of murakkabat (tarkib idhafah). The least number of errors were found in the section of majrurat and majzumat.